Incidence of non-melanocytic skin cancer treated in Australia. Issue 6614 (2nd January 1988) - Giles, Graham G; Marks, Robin; Foley, Peter
Abstract : In 1985, as part of a national random household omnibus survey by a market research company, 30 976 Australians (mostly of European origin) were asked whether they had ever been treated by a doctor for skin cancer. The treating doctor or hospital was then approached for confirmation of the diagnosis of all those people who claimed to have been so treated within the past 12 months. Demographic data were also collected, permitting analysis by age, sex, country of birth, current residence, and skin reaction to strong sunlight. Melanomas accounted for less than 5% of the tumours treated. The world standardised incidence of melanoma was 19/100 000 population. The standardised incidence of treated non-melanocytic skin cancer in Australia was estimated to be 823/100 000. The standardised rates for basal cell carcinoma and squamous cell carcinoma were 657 and 166/100 000 respectively, yielding a standardised rate ratio of about 4:1. Standardised rates based on medically confirmed cases only were 555, 443, and 112/100 000 for all non-melanocytic skin cancers, basal cell carcinomas, and squamous cell carcinomas respectively. Significant differences and trends in incidence were noted with respect to age and sex. Rates in men were higher than those in women but significantly so only after the age of 60. People born in Australia had a rate of 936/100 000 compared with 402/100 000 in British migrants. Rates for non-melanocytic skin cancer showed a gradient with respect to latitude within Australia. The rate in people residing north of 29°S was 1242/100 000 compared with a rate of 489/100 000 in those living south of 37°S. A person's skin reaction to strong sunlight was a good indicator of the risk of skin cancer, tanning ability being inversely related to its incidence. The rate in those who always burnt and never tanned when exposed to strong sunlight was 1764/100 000 compared with a rate of 616/100 000 in those who always tanned and never burnt. These findings have important implications for public education programmes in relation to exposure to sunlight in Australia.